Pulmonary Sarcoidosis following Etanercept Treatment - Kuljeet Bhamra; Richard Stevens (Case Reports in Rheumatology)
Tumour necrosis factor (TNF) is an important cytokine involved in the pathology of a number of inflammatory conditions, and thus blockade with anti-TNF therapies is becoming the cornerstone in managing such diseases. With increasing use, evidence is collected for the association of sarcoid-like granulomatous disease developing after the initiation of anti-TNF-α therapy, with disease reversal after discontinuation.